2017
DOI: 10.18632/oncotarget.22301
|View full text |Cite
|
Sign up to set email alerts
|

Human glioma stem-like cells induce malignant transformation of bone marrow mesenchymal stem cells by activating TERT expression

Abstract: We investigated whether glioma stem-like cells (GSCs) malignantly transformed bone marrow mesenchymal stem cells (tBMSCs) in the tumor microenvironment. Transplantation of enhanced green fluorescence protein (EGFP)-labeled BMSCs into irradiated athymic nude mice was followed by intracranial injection of red fluorescent protein-expressing glioma stem-like cells (SU3-RFP-GSCs). Singly cloned EGFP-BMSCs, harvested from the intracranial tumors showed TERT overexpression, high proliferation, colony formation and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The cells were stained with Alizarin Red S to detect calcium deposition ( 23 ). The BMSCs were washed three times with PBS and then fixed with 70% ethanol for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were stained with Alizarin Red S to detect calcium deposition ( 23 ). The BMSCs were washed three times with PBS and then fixed with 70% ethanol for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that BMSCs have a similar self-renewal ability as cancer cells, and possess the ability to transform spontaneously in vitro. It has also been suggested that tumors may transform from highly invasive mesenchymal stem cells [ 37 ], especially in the tumor microenvironment [ 38 ]. In addition, Japanese scientists confirmed that there was still a significant difference in the expression of proliferating genes between BMSCs and cancer cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glioma stem cells (GSCs) are also able to induce malignant transformation of BMSCs by activating TERT expression. Besides, transformed BMSCs are able to generate subcutaneous tumors when transplanted in athymic nude mice [55]. In addition, C6 glioma-conditioned medium (GCM) induces malignant transformation of MSCs.…”
Section: Discussionmentioning
confidence: 99%